1977
DOI: 10.2466/pms.1977.45.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and Proxemic Behavior

Abstract: The relationship between proxemic behavior and neuroticism was examined. 50 male and 43 female subjects individually self-selected seats in a classroom where they were administered the Eysenck Personality Inventory by one of four experimenters (two male, two female). A significant relationship was found between proxemic distance and both neuroticism and experimenter's sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, since RWA was not measured in this study, future studies are needed to test whether RWA mediates the relationships between extraversion and conscientiousness with stigma. Previous studies on proxemics and neuroticism suggested that people who scored higher on neuroticism had a general tendency to prefer more social distance compared to those with lower scores [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, since RWA was not measured in this study, future studies are needed to test whether RWA mediates the relationships between extraversion and conscientiousness with stigma. Previous studies on proxemics and neuroticism suggested that people who scored higher on neuroticism had a general tendency to prefer more social distance compared to those with lower scores [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to personality traits, a number of studies yielded intuitively sensible results. For instance, neuroticism and introversion-variables which may be relevant to self-protection-were found to predict personal space (De Julio & Duffy, 1977;Pedersen, 1973), although it must be noted that there have been many inconsistent findings involving personality traits (see Hayduk, 1983). It should also be noted that several different methods 4 have been used to measure personal space, although all of them are subjective measures, relying on the phenomenological experience of participants (e.g., approaching a target and stopping at a comfortable distance).…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap, this study aimed to shed light on the effect of religiosity on the preferred ID in the male-male, female-female, and male-female interactions. Personality traits have also been investigated in the field of nonverbal behavior (Cole, 2000;De Julio and Duffy, 1977). Ickinger and Morris (2001) observed that individuals who hold a negative attitude toward the world and others maintain a larger ID in their interactions.…”
mentioning
confidence: 99%